2009
DOI: 10.1051/0004-6361/200911619
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rotation on the stability of nuclear burning in accreting neutron stars

Abstract: Hydrogen and/or helium accreted by a neutron star from a binary companion may undergo thermonuclear fusion. Different burning regimes are discerned at different mass accretion rates. Theoretical models predict helium fusion to proceed as a thermonuclear runaway for accretion rates below the Eddington limit and as stable burning above this limit. Observations, however, place the boundary close to 10% of the Eddington limit. We study the effect of rotationally induced transport processes on the stability of heli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
116
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(127 citation statements)
references
References 44 publications
11
116
0
Order By: Relevance
“…For example, mHz quasi-periodic oscillations (QPOs) resulting from marginally-stable thermonuclear burning are observed at an inferred mass-accretion rate that is a factor ≃10 lower than the theoretical predictions (e.g., Revnivtsev et al 2001;Altamirano et al 2008;Keek et al 2009;Linares et al 2012). This can be reconciled if there is an additional heat flux coming from the crust.…”
Section: Introductionmentioning
confidence: 90%
“…For example, mHz quasi-periodic oscillations (QPOs) resulting from marginally-stable thermonuclear burning are observed at an inferred mass-accretion rate that is a factor ≃10 lower than the theoretical predictions (e.g., Revnivtsev et al 2001;Altamirano et al 2008;Keek et al 2009;Linares et al 2012). This can be reconciled if there is an additional heat flux coming from the crust.…”
Section: Introductionmentioning
confidence: 90%
“…The authors found that the mixing was more effective for slowly rotating stars. Keek et al (2009) performed more sophisticated, yet still 1D, numerical simulations showing that mixing could also be important for fast spins. They also found that mixing due to other, purely hydrodynamical effects could be important for high-enough spins.…”
Section: Another Mechanism Affecting the Burst Rate: Mixingmentioning
confidence: 99%
“…Even at low accretion rates, the burning rate and the energy release may be above the instability threshold and the bursts begin; then, the frequency of the bursts increases with accretion rate. At the same time, accretion releases heat that eventually stabilizes the burning, preventing any bursting (Fujimoto et al 1981;Bildsten & Brown 1997;Bildsten 1998;Cumming & Bildsten 2000;Keek et al 2009;Zamfir et al 2014). The amount of heat generation from accretion comes from the gravitational energy released at the moment of accretion, the compressional heat due to the extra weight of the accumulated material, and the heat of further reactions that take place deeper than the burning layer (Cumming & Bildsten 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations